Potential removal of arsenite from contaminated water using a fixed bed column packed with TiO2-impregnated pomegranate peel powder - Poudel, Bhoj Raj; Aryal, Ram Lochan; Ghimire, Kedar Nath; Paudyal, Hari; Pokhrel, Megh Raj (BIBECHANA, 2024)
A dynamic biosorption of arsenite in a fixed bed column packed with TiO2 impregnated pomegranate peel (PP@TiO2) has been investigated in this work, which is important to identify the effectiveness and affordability of an adsorbent in actual practice. To create an active adsorption site for As (III) ions, pomegranate peel powder (PP) was impregnated with TiO2. Under various operating parameters, the performance of a column packed with PP@TiO2 for adsorbing As (III) ions was evaluated. Breakthrough curve modelling showed that the bed depth service time (BDST) and Thomas models agreed well with the experimental data. The maximum column capacity of PP@TiO2 using the Thomas model was found to have resembled experimental value with high values of coefficient of determination. Therefore from these results, we may anticipate that PP@TiO2 can be a strong contender for the treatment of wastewater that has traces amount of the As (III) ion in a fixed bed system.